Thermoelectric Properties of Nanostructured Materials Based on Lead Telluride - R.Ya.В Yavorskyj; V.S. Blahodyr; O.I. Varunkiv; T.O. Parashchuk (Журнал нано- та електронної фізики)
The results of the thermoelectric properties study obtained by pressing the materials powder on the basis of two types of lead telluride are shown: mechanical mixtures of basic microdisperse PbTe and nanodispersed additives ZnO or TiO2; alloyed by antimony lead telluride and alloyed by silver lead-tin telluride in amount that exceeds the limit of impurity solubility, in order to provide additional phases. It has been established that the system heterophasicity, especially of the second type, provides the materials obtaining with low value of the thermal conductivity coefficient, which allows receiving effective thermoelectric materials with the thermoelectric figure of merit coefficient пЂѕВ 1.0.